Composite solid electrolyte for lithium secondary battery and method for producing same
The method of forming a hydrogel with a ceramic compound and sintering to create a ceramic ion conductor, then immersing in a polymer and lithium salt solution, addresses the challenge of low ionic conductivity in conventional composite solid electrolytes for lithium secondary batteries, resulting in improved lithium ion mobility and electrolyte performance.
Patent Information
- Application Number
- JP2024549544
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-05-31
- Filing Date
- 2023-05-31
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-05-31
AI Technical Summary
Conventional composite solid electrolytes for lithium secondary batteries face challenges in achieving uniform dispersion of inorganic substances within the polymer solution, leading to non-uniform inorganic particle distribution and low ionic conductivity.
A method is developed to produce a composite solid electrolyte by forming a hydrogel of a first polymer with a ceramic compound containing crosslinkable functional groups, sintering to create a ceramic ion conductor, and then immersing and drying this conductor in a solution containing a second polymer and a lithium salt to enhance ionic conductivity.
The approach results in a composite solid electrolyte with improved lithium ion conductivity, as the ceramic ion conductor with a cross-linked structure facilitates better mobility of lithium ions, enhancing the overall performance of the electrolyte.
Smart Images

Figure 2025511446000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0067013 filed on May 31, 2022 and Korean Patent Application No. 10-2023-0070195 filed on May 31, 2023, and incorporates all contents disclosed in the documents of said Korean patent applications as part of this specification.
[0002] The present invention relates to a composite solid electrolyte for a lithium secondary battery and a method for producing the same. [Background technology]
[0003] Lithium-ion batteries that use liquid electrolytes have a structure in which the negative and positive electrodes are separated by a separator, and if the separator is damaged due to deformation or external impact, a short circuit may occur, which may lead to the risk of overheating or explosion. Therefore, the development of a solid electrolyte that can ensure safety in the field of lithium-ion secondary batteries is a very important issue.
[0004] Lithium secondary batteries using solid electrolytes have the advantages of increased safety and the prevention of electrolyte leakage, improving battery reliability, and facilitating the production of thin batteries. In addition, because lithium metal can be used in the negative electrode, the energy density can be improved, and as a result, they are expected to be used in small secondary batteries as well as high-capacity secondary batteries for electric vehicles, and are attracting attention as next-generation batteries.
[0005] Among solid electrolytes, polymer solid electrolytes may use polymer materials having ion conductivity or inorganic materials such as oxides or sulfides having ion conductivity. Composite solid electrolytes that combine polymer materials and inorganic materials have also been proposed.
[0006] Such conventional composite solid electrolytes are manufactured by preparing a solution or slurry in which a polymer and an inorganic material are mixed and dispersed, and then solution casting the solution onto a substrate and drying the solution at a high temperature. However, the conventional composite solid electrolyte manufacturing technology has a limitation in that the inorganic material is not uniformly dispersed in the polymer solution, resulting in non-uniform inorganic particle distribution in the composite solid electrolyte, making it difficult to manufacture a composite solid electrolyte with improved ionic conductivity.
[0007] In order to overcome these limitations of conventional composite solid electrolytes, there is a need to develop a technology that can uniformly disperse polymers and inorganic materials and improve the ionic conductivity of a composite solid electrolyte including the same. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Korean Patent Publication No. 2017-0045011 Summary of the Invention [Problem to be solved by the invention]
[0009] It is an object of the present invention to provide a composite solid electrolyte with improved ionic conductivity.
[0010] It is another object of the present invention to provide a method for preparing a composite solid electrolyte having improved ionic conductivity.
[0011] Another object of the present invention is to provide an all-solid-state battery including a composite solid electrolyte with improved ionic conductivity. [Means for solving the problem]
[0012] To achieve the above object, the present invention provides a method for producing a composite solid electrolyte for a lithium secondary battery, comprising: (S1) preparing a first composite by forming a hydrogel of a first polymer having a cross-linkable functional group (side chain) from a solution containing the first polymer and a ceramic compound; (S2) sintering the first composite to prepare a ceramic ion conductor; and (S3) immersing the ceramic ion conductor in a solution containing a second polymer and a lithium salt, and drying the solution to prepare a second composite.
[0013] The present invention also provides a composite solid electrolyte for a lithium secondary battery, comprising: a ceramic ion conductor comprising a ceramic compound; a second polymer; and a lithium salt, wherein the ceramic ion conductor comprises a cross-linked structure comprising the ceramic compound.
[0014] The present invention also provides an all-solid-state battery comprising the composite solid electrolyte for lithium secondary batteries. Effect of the Invention
[0015] The composite solid electrolyte according to the present invention can effectively improve the ionic conduction of lithium ions by forming a ceramic ionic conductor containing a ceramic compound. [Brief description of the drawings]
[0016] [Figure 1] 1 is a photographed image of a polymer hydrogel according to an embodiment of the present invention. [Diagram 2] 1 is an image showing a ceramic ion conductor formed after sintering a polymer hydrogel according to an embodiment of the present invention. [Diagram 3] 1 is a scanning electron microscope (SEM) photograph of a ceramic compound powder (pristine LLZO) according to an embodiment of the present invention. [Figure 4]1 is a scanning electron microscope (SEM) photograph of a ceramic ion conductor according to an embodiment of the present invention. [Diagram 5] 1 is a photographed image of a polymer hydrogel according to an embodiment of the present invention. [Figure 6] 1 is a photographed image of a ceramic ion conductor according to an embodiment of the present invention. [Figure 7] 2 is a photographed image of a ceramic ion conductor according to Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will now be described in further detail to aid in the understanding of the present invention.
[0018] The terms and words used in this specification and the claims should not be interpreted in a limited manner based on their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that corresponds to the technical idea of the present invention, based on the principle that the inventor can appropriately define the concept of the term in order to best describe his / her invention.
[0019] Method for producing composite solid electrolyte for lithium secondary battery A method for preparing a composite solid electrolyte according to an embodiment of the present invention may include the following steps: (S1) preparing a first composite by forming a hydrogel of a first polymer having a cross-linkable functional group (side chain) from a solution containing a ceramic compound and the first polymer; (S2) sintering the first composite to produce a ceramic ion conductor; (S3) immersing the ceramic ion conductor in a solution containing a second polymer and a lithium salt, and drying the solution to prepare a second composite.
[0020] In the method for producing the composite solid electrolyte, a hydrogel of the first polymer is produced from a solution containing the first polymer and the ceramic compound, so that the ceramic compound can be uniformly dispersed in the first polymer solution. In addition, a ceramic ion conductor is produced using the hydrogel of the first polymer, so that the ion conduction of lithium ions is improved, and a composite solid electrolyte with improved ion conductivity can be produced.
[0021] Hereinafter, each step of the method for preparing the composite solid electrolyte according to the present invention will be described in detail.
[0022] In the present invention, in step (S1), a first composite can be prepared by forming a hydrogel of the first polymer from a solution containing a first polymer having a cross-linkable functional group (side chain) and a ceramic compound.
[0023] The first composite can be prepared through hydrogelation of the first polymer.
[0024] Conventional composite solid electrolytes are prepared by mixing and dispersing a polymer and an inorganic material to prepare a solution, coating the solution on a substrate using a method such as solution casting, and then drying to prepare a final composite solid electrolyte film. However, such composite solid electrolytes have a problem in that the inorganic material is not uniformly dispersed in the polymer solution, resulting in non-uniform inorganic particle distribution in the final composite solid electrolyte film, resulting in low ionic conductivity.
[0025] Therefore, the present inventors have completed a composite solid electrolyte having improved ionic conductivity by efficiently producing a ceramic ion conductor by uniformly dispersing particles of the ceramic compound in the first composite through hydrogelation of the first polymer and sintering the first composite.
[0026] The hydrogelation of the first polymer may include physical or chemical cross-linking of the first polymer, and the physical or chemical cross-linking may include a cross-linked structure between the first polymer containing a cross-linking functional group and the ceramic compound.
[0027] In the present invention, the cross-linked structure can include (a) cross-links between cross-linkable functional groups, and (b) cross-links between the cross-linkable functional groups and the ceramic compound.
[0028] The (a) cross-linking bond between the cross-linking functional groups can include a hydrogen bond between the cross-linking functional groups, and for example, the hydrogen bond may be a hydrogen bond between OH-.
[0029] The crosslinking between the (b) crosslinkable functional group and the ceramic compound may include a bond due to Lewis acid-base interaction, for example, the bond may be a bond between an -OH group and Li. The crosslinking between the (b) crosslinkable functional group and the ceramic compound may be a bond due to Lewis acid-base interaction, and may be a crosslink in the form of a metal-ligand bond.
[0030] In addition, the (b) crosslinking between the crosslinkable functional group and the ceramic compound prevents aggregation between particles of the ceramic compound and allows the particles of the ceramic compound to be uniformly dispersed in the hydrogel. Therefore, the ion conductivity of the composite solid electrolyte can be improved through a ceramic ion conductor manufactured by forming a hydrogel of the first polymer to manufacture a first composite and then sintering the first composite.
[0031] The cross-linked structure improves the mobility of lithium ions within the electrolyte, making it possible to provide a composite solid electrolyte with improved ionic conductivity.
[0032] In the present invention, the cross-linkable functional group contained in the first polymer may have a property capable of forming a cross-linked structure by forming bonds as described in (a) and (b).
[0033] For example, the cross-linkable functional group may include one or more selected from the group consisting of a hydroxyl group, a carboxyl group, and an amide group.
[0034] In addition, the weight average molecular weight (Mw) of the polymer containing the crosslinkable functional group may be 80,000 g / mol to 130,000 g / mol, specifically, 80,000 g / mol or more, 83,000 g / mol or more, or 85,000 g / mol or more, and 90,000 g / mol or less, 110,000 g / mol or less, or 130,000 g / mol or less. If the weight average molecular weight (Mw) of the polymer containing the crosslinkable functional group is less than 80,000 g / mol, the bond by the crosslinkable functional group may not be formed sufficiently to obtain a crosslinked structure. If the weight average molecular weight (Mw) of the polymer containing the crosslinkable functional group exceeds 130,000 g / mol, the entanglement of the polymer chain increases in the polymer solution used in the manufacturing process, and the solvent penetration rate into the inside of the polymer chain decreases. This may accelerate gelation of the polymer, reduce the solubility of the polymer, and inhibit smooth bonding via cross-linking functional groups, making it difficult to form a cross-linked structure.
[0035] In addition, the first polymer having a cross-linkable functional group may include at least one selected from the group consisting of polyvinyl alcohol (PVA), gelatin, methylcellulose, agar, dextrin, poly(vinyl pyrrolidone), poly(acryl amide), poly(acrylic acid) (PAA), starch-carboxymethyl cellulose, hyaluronic acid-methylcellulose, chitosan, poly(N-isopropylacrylamide), and amino-terminated PEG. Preferably, the polymer having a cross-linkable functional group may be PVA, which can efficiently perform phase separation between the PVA and a solvent upon freezing during the preparation of a composite solid electrolyte, and can be advantageous in forming a cross-linked structure through the (a) and (b) bonds derived from the cross-linkable functional group of the PVA that is phase-separated from the solvent.
[0036] In one embodiment of the present invention, the cross-linked structure can be formed by freezing and thawing a solution containing the first polymer and the ceramic compound.
[0037] In the freezing process, the first polymer and water contained in the polymer aqueous solution containing the cross-linkable functional group can undergo phase separation. The phase separation can be induced because the strength of the hydrogen bonds between the cross-linkable functional group and the water molecules is stronger than that between the cross-linkable functional group and the water molecules. The water molecules aggregated by the hydrogen bonds with the water molecules exist in an icy state (ice phase) through the freezing process. As a result, the number of cross-linkable functional groups that form hydrogen bonds through interaction with the water molecules is significantly reduced.
[0038] Due to the phase separation, the inside of the hydrogel is divided into (i) a polymer-poor phase and (ii) a polymer-rich phase.
[0039] The (i) polymer-poor phase is a portion that contains water molecules aggregated by hydrogen bonds with water molecules, and exists in an icy state (ice phase), which can also be called a free water state.
[0040] The (ii) polymer-rich phase is a portion containing a polymer that has been phase-separated from water. The phase-separated polymer is a polymer containing a cross-linking functional group that has been freed from interactions with water molecules, and after phase separation, it is in a free state and does not form crystals through regular folding, but exists in an amorphous state with relatively free behavior, which is called an amorphous polymer chain.
[0041] In addition, some of the cross-linkable functional groups contained in the phase-separated polymer form localized crystallites, which act as cross-linkable junction points to form a cross-linked structure including the bonds (a) and (b).
[0042] In addition, in a thawing process after the freezing process, the ice contained in the (i) polymer-poor phase melts and evaporates, thereby producing a composite solid electrolyte with an increased free volume.
[0043] The freezing can be performed by appropriately selecting conditions that can freeze the hydrogel. For example, the freezing temperature can be -30°C to -10°C, and specifically, the freezing temperature can be -30°C or higher, -25°C or higher, or -23°C or higher, and can be -18°C or lower, -15°C or lower, or -10°C or lower. If the freezing temperature is lower than -30°C, cracks may occur in the hydrogel, and if it exceeds -10°C, phase separation between the polymer and water may not be sufficient, making it difficult to form an amorphous polymer chain region. The freezing can be performed by taking into consideration the time required for sufficient freezing within a range of 20 hours to 30 hours.
[0044] The thawing can be performed by appropriately selecting conditions that allow the frozen hydrogel to be thawed to an extent that it can be used as a composite solid electrolyte. For example, the thawing temperature may be 15°C to 35°C, or may be room temperature (25°C). If the thawing temperature is less than 15°C, the efficiency of drying water after thawing (ice melting) may decrease, and if it exceeds 35°C, the hydrogel may shrink and wrinkle or warp may occur.
[0045] In one embodiment of the present invention, the cross-linked structure may be formed by adding a chemical cross-linker to a solution containing the first polymer and the ceramic compound.
[0046] The cross-linked structure can be formed by physical cross-linking via the above-mentioned freezing and thawing process, as well as by chemical cross-linking using a chemical cross-linking agent.
[0047] The cross-linking involving the first polymer may include a chemical cross-linking, and the chemical cross-linking may be performed by forming a cross-link between the first polymer including a cross-linkable functional group and the ceramic compound using a chemical cross-linker to form a cross-linked structure.
[0048] In the cross-linking including the first polymer, chemical cross-linking can be performed by adding a chemical cross-linker to a mixed solution including the first polymer and the ceramic compound to form a chemical cross-linking of the first polymer.
[0049] The chemical crosslinking agent can form bonds between a first polymer containing a crosslinkable functional group, or between a first polymer containing a crosslinkable functional group and a ceramic compound.
[0050] The chemical crosslinking agent may include at least one selected from the group consisting of boric acid, glutaraldehyde, inorganic salts, and metal salts, but is not limited to these examples, and any chemical crosslinking agent that forms a hydrogel of the first polymer may be used.
[0051] In the first composite, the ceramic compound may include 1 part by weight or more and less than 10 parts by weight relative to 1 part by weight of the first polymer. More specifically, the weight ratio of the first polymer and the ceramic compound may be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, or 1:9. If the ceramic compound includes less than 1 part by weight relative to 1 part by weight of the first polymer, the ceramic compounds are not bonded smoothly after the sintering process in the following step (S2), making it difficult to form a ceramic ion conductor with a cross-linked structure, and the mechanical properties are also weak, making it easy to break or be destroyed, making it impossible to manufacture a composite solid electrolyte. In addition, if the ceramic compound is contained in an amount of more than 10 parts by weight per part by weight of the first polymer, the ceramic compound is not uniformly dispersed in the first polymer, and the ceramic compound particles aggregate with each other, resulting in phase separation between the first polymer and the aggregated ceramic compound particles, making it difficult to form a ceramic ion conductor, resulting in a composite solid electrolyte having reduced ion conductivity.
[0052] In the present invention, in the step (S2), the first composite body may be sintered to prepare a ceramic ion conductor.
[0053] As used herein, sintering refers to the process of subjecting the first composite to sufficient temperature and pressure to form it into a harder mass of particles.
[0054] The ceramic ion conductor may be prepared by sintering the first composite body, pyrolyzing the hydrogel of the first polymer, and sintering the remaining ceramic compound particles.
[0055] Through the sintering process, the hydrogel of the first polymer acts as a support to allow the ceramic compound particles to be connected to each other, and the ceramic compound particles are connected to each other to form a ceramic ion conductor having a cross-linked structure.
[0056] The ceramic ion conductor may serve to form an ion conduction path for lithium ions.
[0057] The sintering can be performed by appropriately selecting conditions that allow the hydrogel of the first polymer to be thermally decomposed, and the ceramic compound particles to be connected to each other to form an ion conductor with a cross-linked structure. For example, the sintering can be performed at a temperature of 800°C to 1300°C, and more specifically, the sintering temperature may be 850°C or more, 900°C or more, or 950°C or more, or 1300°C or less, 1250°C or less, or 1200°C or less.
[0058] In the present invention, in the step (S3), the ceramic ion conductor may be immersed in a solution containing a second polymer and a lithium salt, and then dried to prepare a second composite body.
[0059] The second composite body contains the ceramic ion conductor, so that a composite solid electrolyte having improved ion conductivity can be produced.
[0060] The second polymer may be a polymer having excellent solubility in lithium salt, such that the polymer solution can easily permeate the ceramic ion conductor and the final composite solid electrolyte can be easily produced. Specific examples of the second polymer include polyvinyl alcohol (PVA), polyethylene oxide (PEO), polyacrylate, poly(methyl methacrylate, PMMA), PSTFSI, polyurethane, nylon, poly(dimethylsiloxane), gelatin, methylcellulose, agar, dextrin, poly(vinyl pyrrolidone), poly(acryl amide), poly(acrylic acid), starch-carboxymethyl cellulose, hyaluronic acid-methylcellulose, chitosan, poly(N-isopropylacrylamide), and amino-terminated polyethylene glycol. PEG) may be included.
[0061] In the present invention, the lithium salt is contained in a dissociated state within the structure formed by the ceramic ion conductor, thereby improving the ionic conductivity of the composite solid electrolyte. Also, the lithium salt is mainly dissociated within the second polymer, thereby compensating for the loss of lithium ions generated from the ceramic compound particles during the high-temperature sintering process in step (S2).
[0062] The lithium salts include (CF3SO2)2NLi (Lithium bis(trifluoromethanesulphonyl)imide, LiTFSI), (FSO2)2NLi (Lithium bis(fluorosulfonyl)imide, LiFSI), LiNO3, LiOH, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, LiSCN, and LiC(CF3SO2)3.
[0063] The ceramic ion conductor prepared in step (S2) may be immersed or coated in a solution containing a second polymer and a lithium salt, and then dried to prepare the second composite body. The immersion or coating and drying may be repeated several times.
[0064] The molar ratio ([Li] / [G]) of the second polymer to the lithium ([Li]) of the lithium salt may be 0.1 to 0.5, specifically, 0.1 or more, 0.2 or more, or 0.3 or more, and 0.4 or less, or 0.5 or less. If the molar ratio ([Li] / [G]) is less than 0.1, the content of the lithium salt may decrease, and the ionic conductivity of the composite solid electrolyte may decrease. If the molar ratio ([Li] / [G]) is more than 0.5, the ionic conductivity may decrease due to the aggregation of lithium ions. Therefore, in the composite solid electrolyte according to the present invention, the second composite needs to have a composition of the second polymer and an appropriate amount of lithium salt.
[0065] Composite solid electrolyte for lithium secondary batteries The composite solid electrolyte for a lithium secondary battery according to the present invention includes a ceramic ion conductor including a ceramic compound; a second polymer; and a lithium salt, and the ceramic ion conductor may include a cross-linked structure including the ceramic compound.
[0066] Conventional composite solid electrolytes are manufactured by coating or dispersing a solution or slurry of a mixture of polymer and inorganic material on a substrate by a method such as solution casting, and then drying the coated solution or slurry. However, this method has a problem that the ionic conductivity of the solid electrolyte is not improved due to non-uniform dispersion and precipitation of inorganic material in the polymer solution.
[0067] To improve this, the present invention provides a composite solid electrolyte including a ceramic ion conductor having a cross-linked structure that forms an ion conduction path for lithium ions, a polymer, and a lithium salt. The ceramic ion conductor has ceramic compound particles uniformly dispersed therein, and can play a role in improving the ion conductivity of the composite solid electrolyte.
[0068] The ceramic compound may be an oxide-based or phosphate-based solid electrolyte. The oxide-based or phosphate-based solid electrolyte may be a garnet-type lithium-lanthanum-zirconium oxide (LLZO, Li7La3Zr2O 12 ), perovskite-type lithium-lanthanum-titanium oxide (LLTO, Li 3x La 2 / 3-x TiO3), phosphate-based NASICON-type lithium-aluminum-titanium phosphate (LATP, Li 1+x Al x Ti 2-x (PO4)3), lithium aluminum germanium phosphate (LAGP, Li 1.5 Al 0.5 Ge 1.5The oxide- or phosphate-based solid electrolytes have a very high grain boundary resistance, and therefore require a sintering process at 1000°C or higher. This causes problems such as lithium volatilization at high temperatures, phase transition, and impurity phase formation. However, oxide- or phosphate-based solid electrolytes generally have a maximum sintering temperature of 10 -4 ~10 -3 It has the advantages of having an ionic conductivity value of 100 S / cm, being stable in a high voltage region, being stable in air, and being easy to synthesize and handle.
[0069] Therefore, the first polymer according to the present invention can be mixed with a different material to prepare a hybrid solid electrolyte, thereby making it possible to compensate for the shortcomings of each material.
[0070] The oxide-based or phosphate-based solid electrolyte has high high-temperature stability since it does not easily burn or ignite even under high-temperature conditions of 400° C. or more. Therefore, when the ceramic ion conductor includes the oxide-based or phosphate-based solid electrolyte, it can improve the mechanical strength as well as the high-temperature stability and ionic conductivity of the composite solid electrolyte for a lithium secondary battery.
[0071] The second polymer and the lithium salt are as described above.
[0072] In one embodiment of the present invention, the ceramic ionic conductor may include a cross-linked structure that includes a ceramic compound.
[0073] The ceramic ion conductor may include a cross-linked structure formed by connecting particles of the ceramic compound to each other.
[0074] The ceramic ion conductor may serve to form an ion conduction path for lithium ions.
[0075] The specific method for producing the ceramic ion conductor and the specific ceramic compound are as described above.
[0076] In the present invention, the composite solid electrolyte may be in the form of a free-standing film. The free-standing film refers to a film that can maintain a film shape by itself without a separate support at room temperature and pressure.
[0077] The free-standing film exhibits elasticity and minimizes brittleness, and has properties as a support that stably contains lithium ions, making it suitable for use as a composite solid electrolyte.
[0078] In the present invention, the ionic conductivity of the composite solid electrolyte is 10 -5 It may be S / cm or more.
[0079] Although the composite solid electrolyte is a solid electrolyte as described above, it exhibits ionic conductivity at a level equal to or higher than that of conventional liquid electrolytes, and can improve the performance of all-solid-state batteries.
[0080] All solid state battery The present invention also relates to an all-solid-state battery including the composite solid electrolyte, the all-solid-state battery including a negative electrode, a positive electrode, and a composite solid electrolyte interposed between the negative electrode and the positive electrode, the composite solid electrolyte having the above-mentioned characteristics.
[0081] Specifically, the composite solid electrolyte contains a ceramic ion conductor and improves the ion conduction of lithium ions, making it suitable as an electrolyte for an all-solid-state battery.
[0082] In the present invention, the positive electrode included in the all-solid-state battery may include a positive electrode active material layer, and the positive electrode active material layer may be formed on one surface of a positive electrode current collector.
[0083] The positive electrode active material layer includes a positive electrode active material, a binder, and a conductive material.
[0084] The positive electrode active material is not particularly limited as long as it is a material capable of reversibly absorbing and releasing lithium ions. Examples of the positive electrode active material include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), Li[Ni x Co y Mn z M v ]O2 (wherein M is any one or more elements selected from the group consisting of Al, Ga, and In; 0.3≦x<1.0, 0≦y, z≦0.5, 0≦v≦0.1, and x+y+z+v=1), Li (Li a M b-a-b’ M' b’ )O 2-c A c (wherein, 0≦a≦0.2, 0.6≦b≦1, 0≦b'≦0.2, 0≦c≦0.2; M includes Mn and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn, and Ti; M' is at least one selected from the group consisting of Al, Mg, and B, and A is at least one selected from the group consisting of P, F, S, and N), or a compound substituted with one or more transition metals; 1+y Mn 2-y Lithium manganese oxides such as LiMnO4 (where y is 0-0.33), LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, Cu2V2O7; and the chemical formula LiNi 1-y Ni-site type lithium nickel oxide represented by MyO2 (where M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y=0.01-0.3); chemical formula LiMn 2-y M yExamples of such compounds include, but are not limited to, lithium manganese composite oxides expressed as Li2Mn3MO8 (where M=Co, Ni, Fe, Cr, Zn, or Ta, and y=0.01-0.1) or Li2Mn3MO8 (where M=Fe, Co, Ni, Cu, or Zn); LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion; disulfide compounds; and Fe2(MoO4)3.
[0085] In addition, the positive electrode active material may be included in an amount of 40 to 80 wt % based on the total weight of the positive electrode active material layer. Specifically, the content of the positive electrode active material may be 40 wt % or more or 50 wt % or more, and 70 wt % or less or 80 wt % or less. If the content of the positive electrode active material is less than 40 wt %, the connectivity between the wet positive electrode active material layer and the dry positive electrode active material layer may be insufficient, and if it exceeds 80 wt %, the mass transfer resistance may be large.
[0086] The binder is a component that aids in bonding the positive electrode active material to the conductive material and the current collector, and is preferably a rubber such as styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polybutadiene ... The binder may include at least one selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethylcellulose, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethylcellulose, hydroxypropylcellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethylcellulose, cyanoethylsucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride, and poly(vinylidene fluoride)-hexafluoropropene. Preferably, the binder may include at least one selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethylcellulose, polyacrylic acid, lithium polyacrylate, and polyvinylidene fluoride.
[0087] The binder may be included in an amount of 1 wt% to 30 wt% based on the total weight of the positive electrode active material layer, and specifically, the binder content may be 1 wt% or more or 3 wt% or more, and 15 wt% or less or 30 wt% or less. If the binder content is less than 1 wt%, the adhesive strength between the positive electrode active material and the positive electrode current collector may decrease, and if it exceeds 30 wt%, the adhesive strength is improved, but the content of the positive electrode active material may decrease accordingly, resulting in a decrease in battery capacity.
[0088] The conductive material is not particularly limited as long as it prevents side reactions in the internal environment of the all-solid-state battery, does not induce chemical changes in the battery, and has excellent electrical conductivity. Representative examples include graphite or conductive carbon. Examples of the conductive material include graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, denka black, thermal black, channel black, furnace black, lamp black, summer black, and other carbon blacks; carbon-based substances having a graphene or graphite crystal structure; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives. These may be used alone or in combination of two or more kinds, but are not necessarily limited thereto.
[0089] The conductive material may be contained in an amount of 0.5 wt% to 30 wt% based on the total weight of the positive electrode active material layer, and specifically, the content of the conductive material may be 0.5 wt% or more or 1 wt% or more, and 20 wt% or less or 30 wt% or less. If the content of the conductive material is too small, such as less than 0.5 wt%, it may be difficult to expect an improvement in electrical conductivity or the electrochemical properties of the battery may be deteriorated, and if the content is too large, such as more than 30 wt%, the amount of the positive electrode active material may be relatively small, and the capacity and energy density may be reduced. The method of including the conductive material in the positive electrode is not significantly limited, and a conventional method known in the art, such as coating on the positive electrode active material, may be used.
[0090] The positive electrode current collector supports the positive electrode active material layer and transfers electrons between an external conductor and the positive electrode active material layer.
[0091] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the all-solid-state battery and has high electronic conductivity. For example, the positive electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, palladium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, silver, or the like, or an aluminum-cadmium alloy.
[0092] The positive electrode current collector may have a fine uneven structure or a three-dimensional porous structure on the surface thereof in order to strengthen the bonding force with the positive electrode active material layer, and may include various forms such as a film, sheet, foil, mesh, net, porous body, foam, nonwoven fabric, etc.
[0093] The positive electrode may be prepared according to a conventional method, specifically, by mixing a positive electrode active material, a conductive material, and a binder in an organic solvent to prepare a composition for forming a positive electrode active material layer, coating the composition on a positive electrode current collector, drying the composition, and optionally compressing the composition into a current collector to improve the electrode density. In this case, it is preferable to use an organic solvent that can uniformly disperse the positive electrode active material, the binder, and the conductive material and that can be easily evaporated. Specifically, acetonitrile, methanol, ethanol, tetrahydrofuran, water, isopropyl alcohol, etc. may be used.
[0094] In the present invention, the negative electrode included in the all-solid-state battery may include a negative electrode active material layer, and the negative electrode active material layer may be formed on one surface of a negative electrode current collector.
[0095] The negative electrode active material is lithium (Li + The lithium-containing compound may include a material capable of reversibly intercalating or deintercalating lithium ions, a material capable of reversibly forming a lithium-containing compound by reacting with lithium ions, lithium metal, or a lithium alloy.
[0096] The lithium ion (Li +The material capable of reversibly inserting or de-inserting lithium ions (Li) may be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + The material capable of reacting with lithium (Li) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0097] Preferably, the negative electrode active material is lithium metal, specifically, in the form of a lithium metal thin film or lithium metal powder.
[0098] The negative electrode active material may be included in an amount of 40 to 80 wt % based on the total weight of the negative electrode active material layer. Specifically, the content of the negative electrode active material may be 40 wt % or more or 50 wt % or more, or 70 wt % or less or 80 wt % or less. If the content of the negative electrode active material is less than 40 wt %, the connectivity between the wet negative electrode active material layer and the dry negative electrode active material layer may be insufficient, and if it exceeds 80 wt %, the mass transfer resistance may be large.
[0099] The binder is the same as that described above in the positive electrode active material layer.
[0100] The conductive material is the same as that described above in the positive electrode active material layer.
[0101] The negative electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity, and for example, the negative electrode current collector can be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. Similarly to the positive electrode current collector, the negative electrode current collector can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., having fine irregularities formed on the surface.
[0102] The method for manufacturing the negative electrode is not particularly limited, and the negative electrode may be manufactured by forming a negative electrode active material layer on a negative electrode current collector using a method for forming a layer or film commonly used in the art. For example, methods such as compression bonding, coating, deposition, etc. may be used. In addition, the negative electrode of the present invention also includes a case where a thin metallic lithium film is formed on a metal plate by initial charging after assembling a battery without a thin lithium film on the negative electrode current collector.
[0103] The present invention also provides a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.
[0104] Specific examples of the device include, but are not limited to, power tools that are driven by a battery-type motor; electric vehicles, including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; power storage systems, etc. Preferred examples are shown below to aid in the understanding of the present invention. However, the following examples are merely illustrative of the present invention, and it is obvious to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention, and such changes and modifications naturally fall within the scope of the accompanying claims.
[0105] Preferred examples are shown below to aid in understanding the present invention. The following examples are provided to facilitate understanding of the present invention, and the present invention is not limited thereto.
[0106] In the following examples and comparative examples, ceramic ion conductors containing polymers, ceramic compounds, etc. as shown in Table 1 below were produced, and composite solid electrolytes containing the same were produced.
[0107] [Table 1]
[0108] Example 1: Preparation of composite solid electrolyte (1) Preparation of the complex PVA (Mw: 89,000 g / mol; degree of hydrolysis: >99%) was mixed with DI water to prepare a 10 wt% PVA aqueous solution. A solution was prepared by adding LLZO powder, a ceramic compound, to the PVA aqueous solution. The weight ratio of PVA to LLZO was 1:2.
[0109] The solution was poured into a polycarbonate Petri dish (3 ml), frozen at -20°C for 24 hours, and thawed at 25°C to induce physical cross-linking of the PVA, thereby preparing a composite in the form of a hydrogel.
[0110] (2) Manufacturing of ceramic ionic conductors The hydrogel composite was heated from room temperature to 800°C at a rate of 1°C / min and sintered at 800°C for 2 hours to pyrolyze the PVA hydrogel and sinter the remaining LLZO particles to produce a ceramic ion conductor.
[0111] (3) Manufacturing of composite solid electrolyte A solution containing PEO and LiTFSI was prepared (wherein the molar ratio ([Li] / [O]) of “O” contained in PEO and “Li” contained in the lithium salt was 0.4), and the ceramic ion conductor was immersed in the prepared solution and dried to prepare a composite solid electrolyte.
[0112] Example 2 A composite solid electrolyte was prepared in the same manner as in Example 1, except that LSTP was used instead of the ceramic compound LLZO.
[0113] Example 3 A composite solid electrolyte was prepared in the same manner as in Example 1, except that the weight ratio of the polymer (PVA) and the ceramic compound (LLZO) was 1:10.
[0114] Example 4 A composite solid electrolyte was prepared in the same manner as in Example 1, except that the weight ratio of the polymer (PVA) and the ceramic compound (LLZO) was 10:1.
[0115] Example 5 A composite solid electrolyte was prepared in the same manner as in Example 1, except that instead of the freezing and thawing process, 0.1 ml of boric acid (1 wt% aqueous solution) was added as a chemical cross-linker to 20 ml of the solution containing the PVA and ceramic compound, and the mixture was stirred at 200 rpm for 1 hour using a magnetic stirrer to prepare a composite in the form of a hydrogel through chemical cross-linking.
[0116] Example 6 A composite solid electrolyte was prepared in the same manner as in Example 5, except that the weight ratio of the polymer (PVA) and the ceramic compound (LLZO) was 1:10.
[0117] Example 7 A composite solid electrolyte was prepared in the same manner as in Example 5, except that the weight ratio of the polymer (PVA) and the ceramic compound (LLZO) was 10:1.
[0118] Comparative Example 1 A composite solid electrolyte was prepared in the same manner as in Example 1, except that a solution containing PVA and LLZO was prepared, the solution was applied onto a glass slide as a substrate, and then the solution was dried at 80° C. for 12 hours instead of the freezing and thawing process.
[0119] Comparative Example 2 A composite solid electrolyte was prepared in the same manner as in Example 1, except that PEO (Mw: 4,000,000 g / mol), a polymer having no cross-linking functional group, was used instead of PVA.
[0120] Comparative Example 3 A composite solid electrolyte was prepared in the same manner as in Example 1, except that a 35% aqueous solution of poly(acrylic acid) (Mw: 100,000 g / mol) was used instead of the polymer PVA.
[0121] Experimental Example Experimental Example 1 The ionic conductivity of the film-type composite solid electrolyte prepared in the Examples and Comparative Examples was measured using a test tube with a thickness of 1.7671 cm 2 The composite solid electrolyte was punched out into a circular shape of a desired size, and the punched composite solid electrolyte was placed between two pieces of stainless steel (SS) to prepare a coin cell.
[0122] Resistance was measured using an electrochemical impedance spectrometer (EIS, VM3, Bio Logic Science Instrument) at 25° C. with an amplitude of 10 mV and a scan range of 500 kHz to 20 MHz, and then the ionic conductivity of the composite solid electrolyte was calculated using the following Equation 1.
[0123] [Formula 1]
number
[0124] In the above formula 1, σ i is the ionic conductivity (S / cm) of the composite solid electrolyte, R is the resistance (Ω) of the composite solid electrolyte measured by the electrochemical impedance spectrometer, L is the thickness (μm) of the composite solid electrolyte, and A is the area (cm 2 )
[0125] The ionic conductivity of the composite solid electrolyte calculated using Equation 1, whether or not a hydrogel was formed, whether or not a freestanding film was formed, and the results of observing the appearance of the composite solid electrolyte are shown in Table 2. Here, whether or not a hydrogel was formed (formed: O, not formed: X), whether or not the freestanding film was formed (formed: O, not formed: X), and the appearance of the composite solid electrolyte were observed with the naked eye.
[0126] [Table 2]
[0127] As shown in Table 2, it was confirmed that a hydrogel was formed by subjecting a solution in which the polymer having a cross-linkable functional group and the ceramic compound were mixed in an appropriate weight ratio to a freezing and thawing process, and the hydrogel was sintered to form a ceramic ion conductor, thereby producing a composite solid electrolyte (Examples 1 to 7 and FIGS. 1 to 6).
[0128] Comparative Example 1 was an electrolyte produced using a high-temperature drying process at 80° C., which resulted in the formation of a brittle film without a cross-linked structure, and no ceramic ion conductor was formed after sintering.
[0129] Comparative Examples 2 and 3 were prepared using a polymer that did not contain a cross-linking functional group, and no polymer hydrogel was formed.
[0130] Although the present invention has been described above using limited examples and drawings, the present invention is not limited thereto, and it goes without saying that various modifications and variations can be made by a person having ordinary knowledge in the technical field to which the present invention pertains within the technical spirit of the present invention and the equivalent scope of the claims described below.
Claims
1. (S1) preparing a first composite by forming a hydrogel of the first polymer from a solution containing a first polymer having a cross-linkable functional group (side chain) and a ceramic compound; (S2) sintering the first composite body to produce a ceramic ion conductor; (S3) immersing the ceramic ion conductor in a solution containing a second polymer and a lithium salt and drying the solution to prepare a second composite; A method for producing a composite solid electrolyte for lithium secondary batteries.
2. 2 . The method of claim 1 , wherein the hydrogel of the first polymer includes a cross-linked structure between the first polymer and the ceramic compound. 3 . The method of claim 1 , wherein the hydrogel of the first polymer includes a cross-linked structure between the first polymer and the ceramic compound.
3. 3. The method for producing a composite solid electrolyte for a lithium secondary battery according to claim 2, wherein the cross-linked structure includes: (a) cross-links between cross-linkable functional groups; and (b) cross-links between the cross-linkable functional groups and the ceramic compound.
4. the (a) cross-linking bond between the cross-linkable functional groups includes a hydrogen bond, 4. The method for producing a composite solid electrolyte for a lithium secondary battery according to claim 3, wherein the (b) cross-linking bond between the cross-linkable functional group and the ceramic compound includes a bond due to a Lewis acid-base interaction.
5. 3. The method of claim 2, wherein the cross-linked structure is formed by freezing and thawing a solution including the first polymer and the ceramic compound.
6. 3. The method of claim 2, wherein the cross-linked structure is formed by adding a chemical cross-linker to a solution containing the first polymer and the ceramic compound.
7. The method for producing a composite solid electrolyte for a lithium secondary battery according to claim 5, wherein the freezing is carried out at -30°C to -10°C.
8. The method for producing a composite solid electrolyte for a lithium secondary battery according to claim 5, wherein the thawing is performed at 15°C to 35°C.
9. 2. The method for producing a composite solid electrolyte for a lithium secondary battery according to claim 1, wherein the cross-linkable functional group comprises at least one selected from the group consisting of a hydroxyl group, a carboxyl group, and an amide group.
10. The first polymer having a cross-linking functional group is selected from the group consisting of polyvinyl alcohol (PVA), gelatin, methylcellulose, agar, dextrin, poly(vinyl pyrrolidone), poly(acryl amide), starch-carboxymethyl cellulose, hyaluronic acid-methyl cellulose, and the like.
2. The method for producing the composite solid electrolyte for a lithium secondary battery according to claim 1, comprising at least one selected from the group consisting of N-isopropylacrylamide, N-isopropylacrylamide, chitosan, poly(N-isopropylacrylamide), and amino-terminated polyethylene glycol.
11. A composite solid electrolyte for a lithium secondary battery, comprising: a ceramic ion conductor comprising a ceramic compound; a second polymer; and a lithium salt.
12. 12. The composite solid electrolyte for a lithium secondary battery according to claim 11, wherein the ceramic compound comprises at least one selected from the group consisting of lithium-lanthanum-zirconium oxide (LLZO), lithium-silicon-titanium phosphate (LSTP), lithium-lanthanum-titanium oxide (LLTO), lithium-aluminum-titanium phosphate (LATP), lithium-aluminum-germanium phosphate (LAGP), and lithium-lanthanum-zirconium-titanium oxide (LLZTO) compounds.
13. The second polymer may be selected from the group consisting of polyvinyl alcohol (PVA), polyethylene oxide (PEO), polyacrylate, poly(methyl methacrylate, PMMA), PSTFSI, polyurethane, nylon, poly(dimethylsiloxane), gelatin, methylcellulose, agar, dextrin, poly(vinyl pyrrolidone), poly(acrylamide), and poly(acrylic acid).
12. The composite solid electrolyte for a lithium secondary battery according to claim 11, comprising at least one selected from the group consisting of poly(N-isopropylacrylamide), starch-carboxymethyl cellulose, hyaluronic acid-methylcellulose, chitosan, poly(N-isopropylacrylamide), and amino-terminated polyethylene glycol.
14. The lithium salt is (CF 3 SO 2 ) 2 NLi (Lithium bis(trifluoromethanesulphonyl)imide), LiTFSI, (FSO 2 ) 2 NLi (Lithium bis(fluorosulfonyl)imide, LiFSI), LiNO 3 , LiOH, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 C 10 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, LiSCN and LiC(CF 3 SO 2 ) 3 The composite solid electrolyte for a lithium secondary battery according to claim 11, comprising at least one selected from the group consisting of:
15. 12. The composite solid electrolyte for lithium secondary batteries according to claim 11, wherein the molar ratio of the lithium ([Li]) of the lithium salt to the molar concentration ([G]) of the second polymer is 0.1 to 0.
5.
16. The composite solid electrolyte for a lithium secondary battery according to claim 11, wherein the composite solid electrolyte is in the form of a freestanding film.
17. The ionic conductivity of the composite solid electrolyte is 1.0×10 -5 12. The composite solid electrolyte for a lithium secondary battery according to claim 11, having a specific surface area of 1.5 S / cm or more.
18. An all-solid-state battery comprising the composite solid electrolyte for a lithium secondary battery according to any one of claims 11 to 17.
Citation Information
Patent Citations
Method for preparing porous ceramics by combining gel casting with freeze drying
CN108863394A
High-ionic-conductivity composite solid electrolyte and preparation method thereof
CN110492170A
Composite solid electrolyte with two surfaces and preparation method thereof
CN112151859A
Composite solid electrolyte based on inorganic ceramic three-dimensional aerogel skeleton support and preparation method thereof
CN113270634A
Preparation method of high-strength foamed ceramic under freeze-thaw cycle
CN117800755A